Jerzy Pietrkiewicz — Jan Bolesław Ożóg. Korespondencyjny dialog autentystów (1937–1988) - Moczkodan, Rafał (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2020)
JERZY PIETRKIEWICZ AND JAN BOLESŁAW OŻÓG: AN EPISTOLARY DIALOGUE OF TWO ‘AUTHENTIC’ POETS (1937–1988) The article explores the relationship between Jerzy Pietrkiewicz and Jan Bolesław Ożóg. It is based on the examination of a collection of letters kept at the Jagiellonian Library in Cracow and the Archives of Polish Emigration in Toruń. The two poets met before the Second World War as members of a literary group of ‘authentic’ poets. After the war Pietrkiewicz settled in England and Ożóg remained in Poland. Their friendship continued in the letters they exchanged. The article analyses the themes and problems which they discussed in their letters, in particular the promotion of ‘authentic’ poetry.